2017
DOI: 10.1152/ajpheart.00287.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increases in cardiac contractility on cerebral blood flow in humans

Abstract: The effect of acute increases in cardiac contractility on cerebral blood flow (CBF) remains unknown. We hypothesized that the external carotid artery (ECA) downstream vasculature modifies the direct influence of acute increases in heart rate and cardiac function on CBF regulation. Twelve healthy subjects received two infusions of dobutamine [first a low dose (5 μg·kg·min) and then a high dose (15 μg·kg·min)] for 12 min each. Cardiac output, blood flow through the internal carotid artery (ICA) and ECA, and echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Methodological concerns and regional cerebrovascular reactivity CBF regulation involves a large spectrum of regulatory mechanisms that, in concert, maintain nutrient and oxygen delivery to the brain . MAP, CO and P aCO 2 , for example, have been indicated as important CBF regulators Ogoh et al 2017). Throughout the experimental protocol, both MAP and CO remained unchanged, indicating that the observed tCBF responses were not affected by these variables.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Methodological concerns and regional cerebrovascular reactivity CBF regulation involves a large spectrum of regulatory mechanisms that, in concert, maintain nutrient and oxygen delivery to the brain . MAP, CO and P aCO 2 , for example, have been indicated as important CBF regulators Ogoh et al 2017). Throughout the experimental protocol, both MAP and CO remained unchanged, indicating that the observed tCBF responses were not affected by these variables.…”
Section: Discussionmentioning
confidence: 90%
“…; Ogoh et al . ). Throughout the experimental protocol, both MAP and CO remained unchanged, indicating that the observed tCBF responses were not affected by these variables.…”
Section: Discussionmentioning
confidence: 97%
“…These two vascular beds appear to have different regulatory mechanisms in controlling blood flow [44][45][46]. Previous reports suggest that external cerebral vasculature plays a dynamic role in intracranial CBF regulation [44,47]. In fact, it was shown that changes in external carotid artery are more distinctive than internal carotid artery changes under acute hypotensive and hypertensive conditions in healthy individuals [44,47].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…xia, dynamic or resistance exercise, orthostatic stress and heat stress (Hashimoto et al, 2018;Hirasawa et al, 2016;Ogoh et al, 2013Ogoh et al, , 2014aOgoh et al, , b, 2015bOgoh et al, , 2017bSato et al, 2012a, b;Sato, Ogoh, Hirasawa, Oue, & Sadamoto, 2011). These findings indicate that this heterogeneous CBF response between the anterior and posterior circulation might be attributable to different physiological roles between different brain areas (e.g.…”
Section: Introductionmentioning
confidence: 96%